Modeling and Simulation of Two Wheelchair Accessories for Pushing Doors. Issue 4 (8th August 2018) - Abdullah, Soran Jalal; Shaikh Mohammed, Javeed
ABSTRACT: Independent mobility is vital to individuals of all ages, and wheelchairs have proven to be great personal mobility devices. The tasks of opening and navigating through a door are trivial for healthy people, while the same tasks could be difficult for some wheelchair users. A wide range of intelligent wheelchair controllers and systems, robotic arms, or manipulator attachments integrated with wheelchairs have been developed for various applications, including manipulating door knobs. Unfortunately, the intelligent wheelchairs and robotic attachments are not widely available as commercial products. Therefore, the current manuscript presents the modeling and simulation of a novel but simple technology in the form of a passive wheelchair accessory (straight, arm-like with a single wheel, and arc-shaped with multiple wheels) for pushing doors open from a wheelchair. From the simulations using different wheel shapes and sizes, it was found that the arc-shaped accessory could push open the doors faster and with almost half the required force as compared to the arm-like accessory. Also, smaller spherical wheels were found to be best in terms of reaction forces on the wheels. Prototypes based on the arc-shaped accessory design will be manufactured and evaluated for pushing doors open and dodging or gliding other obstacles.